(untitled) (Research, Society and Development, 2022)
Since March 11, 2020, the world has been experiencing a new coronavirus pandemic, caused by the disease COVID-19, which has resulted in several changes in daily life. Concerns about overloading the healthcare system and fear of contracting the virus may have led to late presentations and worse outcomes for patients with acute conditions. The objective of the study is to identify and report the effects of the pandemic on emergency surgery services. This is an integrative literature review, with a descriptive approach. The bibliographic research had as its guiding question "What are the impacts of the COVID-19 pandemic on surgical emergency services?". The databases used were: SciELO, PubMed and LILACS, based on the descriptors "COVID-19" and "Emergency Medical Services", using the Boolean operator AND. There were no epidemiologically significant changes in terms of gender and age. The number of presentations to urgent and emergency surgical services reduced by 21%. Complication rates increased by 48%, along with the mortality rate, which increased by 12%, and the late presentation rate to emergency services by 37.4%. The pandemic of the new SARS-CoV 2 significantly influenced the assistance of health systems. During this period, there was a reduction in these surgeries and in the number of acute events, such as trauma. Several hypotheses have been postulated to explain this behavior, including social isolation and information broadcast by the media about the situation in hospitals, which increases the delay in seeking emergency services and increases the mortality rate.